A Lesson Study on Teaching Impulse and Momentum in the New Normal - Aileen Mae G. Cañete; Angel Rose J. Hitgano; Ella Marie G. Nuñez; Alisa Mae D. Talamo; Ricka Mae Marie L. Ymas; Joy A. Bellen (Universal Journal of Educational Research)
Impulse and momentum are basic concepts of mechanics introduced in the K to 12 curricula. Despite its basic concepts, students still have difficulties understanding the topic, especially when they are out of school due to the pandemic. After reopening the gates for face–to–face classes in the Philippines, the researchers found a significant reason to conduct a lesson study to improve teaching strategies on the topic. Lesson study is a development process wherein teachers work collaboratively to improve teachers teaching capacity. This study was conducted at Plaridel National High School with 23 participants from Grade 9 Newton (Set A and B). The research was conducted in two cycles using a four – phase lesson study. The research lesson was implemented using a 4A Model lesson plan and the results were taken from the analysis of the lesson study observation sheets, along with the class proficiency level. The researchers used the following strategies to improve teaching, namely; (1) showing mastery of subject matter, (2) reviewing basic mathematical operations, (3) contextualizing the lesson, (4) allowing students to answer questions in mother tongue, (5) using collaborative activities, (6) giving rewards, and (7) applying proper time management. However, the findings still showed that both sets of students achieved beginning proficiency level. Despite the implementation of these strategies, the students still lack basic knowledge of the topic and mathematical operations, and they struggle to understand it. Thus, it is recommended to plan the lesson effectively, utilize other research instruments, and collect feedback from the students.